Penyelenggaraan Perpustakaan Khusus Berdasarkan Standar Nasional Perpustakaan Khusus Nomor 7 Tahun 2022 (Studi Kasus di Pengadilan Negeri Padang Kelas 1A) - Primadiya, Syaharani; Nelisa, Malta (Scinary, 2025)
This study aims to describe the implementation of a special library at the Padang District Court Class 1A based on the National Standard for Special Libraries Number 7 of 2022. This research is a descriptive qualitative research with 3 (three) informants selected through purposive sampling. The data collection was carried out through observation, interview, and documentation. Data validation was carried out by triangulating techniques, by equating the research results obtained based on 3 (three) different data collection techniques which were then analysed through 3 (three) stages, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of a special library in the Class 1A Padang District Court Library has not fully complied with the 6 (six) aspects in the National Standard for Special Libraries Number 7 of 2022. Starting from library collections, facilities and infrastructure, library services, library staff, library organisation, and library management.